Preparation method of aluminum alloy material with high strength and low fatigue crack growth rate
By using two-stage particle size ratio and multi-step process processing in aluminum alloy materials, the heterostructured aluminum alloy material is formed, which solves the problem of inverted relationship between strength and fatigue performance of aluminum alloy materials, and achieves the comprehensive performance improvement of high strength and low fatigue crack propagation rate.
Patent Information
- Application Number
- CN202510093185.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The prior art is difficult to simultaneously increase the strength of aluminum alloy materials and reduce the fatigue crack propagation rate, resulting in the inverted relationship between strength improvement and fatigue performance degradation.
By proportioning the aluminum alloy powder according to the particle size distribution of the two stages, mixing powder, hot isostatic pressure treatment, homogenizing annealing treatment, plastic processing and forming, solid solution treatment, cold deformation treatment and low-temperature aging treatment, heterostructure aluminum alloy material is formed.
The aluminum alloy material preparation with high strength and low fatigue crack propagation rate is achieved, the process is simple and easy to operate, and the conditions for industrial production are met.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an aluminum alloy material, and in particular to a microstructure design and a preparation method capable of simultaneously improving the strength and fatigue crack propagation resistance of the aluminum alloy material, and belongs to the technical field of aluminum alloy materials. Background Art
[0002] Aluminum alloys are the most commonly used lightweight structural materials because of their light weight, high strength, damage resistance, and corrosion resistance. Deformed aluminum alloys, in particular, are widely used in the aviation field. The rapid development of the aviation industry has put forward higher demands on high-performance aluminum alloy materials. Improving the strength of aluminum alloy materials can further effectively achieve lightweight structures; reducing the fatigue crack growth rate of aluminum alloy materials can improve the safety and durability of aviation components. Therefore, the development of aluminum alloy materials with high strength and low fatigue crack growth rate has important practical significance for the development and upgrading of high-performance aviation structural materials.
[0003] Traditional strengthening strategies for aluminum alloys include fine grain strengthening, dispersion strengthening, solid solution strengthening, and dislocation strengthening. However, for the current deformation series aluminum alloys, such as Al-Cu series and Al-Zn series aluminum alloys, the strength improvement has been extremely limited through conventional preparation, processing, and heat treatment processes. Although the strength can be greatly improved through large deformation treatment, its process is complicated and it is difficult to prepare large-scale aluminum alloy components. More importantly, these traditional strengthening strategies inevitably lead to an increase in fatigue crack growth rate, which is not conducive to the damage tolerance design requirements of aviation components. For example, grain refinement, increased dislocation density, and the introduction of high volume fraction dispersed particles will reduce the size of the plastic zone at the fatigue crack tip, resulting in a significant reduction in the passivation effect of the deformation zone at the fatigue crack tip. At the same time, grain refinement will also weaken the deflection and closure effects of the crack path, and will also lead to an increase in the fatigue crack growth rate; while coarse grains can improve crack passivation and closure capabilities, but will reduce strength.
[0004] It can be seen from this that there is an inverted relationship between the strength and fatigue crack growth resistance of aluminum alloys. How to increase the strength while reducing the fatigue crack growth rate is crucial to improving the comprehensive mechanical properties. It is urgent to design a new aluminum alloy microstructure configuration and optimize the precipitation phase characteristics to simultaneously achieve increased static load strength and reduced fatigue crack growth rate. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that it is difficult to achieve simultaneous improvement in the strength and fatigue crack growth resistance of aluminum alloys in the prior art. In view of the problem that the improvement in strength of deformed aluminum alloys leads to an increase in fatigue crack growth rate or a decrease in fatigue crack growth rate leads to a decrease in strength, a technical method with industrial production conditions is provided to simultaneously improve the strength and fatigue crack growth resistance of aluminum alloys.
[0006] The present invention provides a method for preparing a high-strength and low fatigue crack growth rate aluminum alloy material, comprising the following technical scheme: aluminum alloy powder is proportioned according to a two-level particle size distribution, and then powder mixing and hot isostatic pressing treatment, homogenization annealing treatment and plastic processing forming, solid solution treatment and cold deformation treatment, and low-temperature aging treatment are sequentially performed.
[0007] Specifically, the method for preparing the high-strength and low fatigue crack growth rate aluminum alloy material of the present invention comprises the following steps:
[0008] (1) Two-stage particle size ratio: two types of aluminum alloy powders with different particle size distributions are screened, the first stage is fine aluminum alloy powder with an average particle size of 10-60 μm; the second stage is coarse aluminum alloy powder with an average particle size of 50-600 μm; wherein the weight proportion of the fine aluminum alloy powder is 60%-80%;
[0009] (2) Powder mixing, vacuum degassing and hot isostatic pressing: After the fine aluminum alloy powder and the coarse aluminum alloy powder are fully mixed, vacuum degassing and hot isostatic pressing are performed to obtain an aluminum alloy ingot with a density of ≥99.5%;
[0010] (3) homogenization annealing and plastic forming: the aluminum alloy ingot is subjected to homogenization annealing, air-cooled, and then plastic formed to obtain a heterogeneous aluminum alloy material having a coarse-fine grain distribution;
[0011] (4) solution treatment and cold deformation treatment: subjecting the above-mentioned heterogeneous structure aluminum alloy material containing a coarse-fine grain distribution to solution treatment, wherein the solution treatment comprises heating, heat preservation and water quenching steps; immediately after the solution treatment, cold deformation treatment is performed, wherein the deformation amount is 3%-30%, and the interval time with the end of the solution treatment is less than or equal to 1 hour; and the deformed heterogeneous structure aluminum alloy material is obtained;
[0012] (5) Aging treatment: The deformed heterogeneous aluminum alloy material is subjected to aging treatment.
[0013] Preferably, the coarse and fine aluminum alloy powders are obtained by atomizing and then screening.
[0014] Preferably, the particle morphology of the coarse aluminum alloy powder and the fine aluminum alloy powder are both approximately spherical, that is, the average aspect ratio of the coarse and fine aluminum alloy powders is approximately 1, and the particle size distribution is approximately normal distribution.
[0015] Preferably, the ratio of the average particle size of the coarse aluminum alloy powder to the average particle size of the fine aluminum alloy powder is 5-10.
[0016] Preferably, the vacuum degassing and hot isostatic pressing treatment to obtain an aluminum alloy ingot with a density ≥ 99.5% is as follows: the two powders after being fully mixed are first coated with a metal sheath, the heating temperature is 450-550°C, the vacuum degree inside the metal sheath is greater than or equal to 0.1Pa, and then hot isostatic pressing is performed, the pressure is greater than or equal to 100MPa, the hot pressing temperature is 450-550°C, the holding time is 2-8h, and then the heat preservation is continued for 12-24h under no external pressure for homogenization treatment, and finally air cooling is performed, and the density of the obtained aluminum alloy ingot is ≥ 99.5%.
[0017] Preferably, the homogenization annealing treatment parameters in step (3) are: 450-500° C., and a holding time of 6-12 h.
[0018] Preferably, the plastic forming method in step (3) is hot rolling or hot extrusion, wherein the hot rolling is: the rolling start temperature is 420°C, and when the total thickness deformation is 98% or greater than 98%, annealing is performed, the annealing temperature is 400°C, and the temperature is kept for 0.5h. After air cooling, cold rolling is performed, and aluminum alloy thin plates are formed through multiple rolling processes. The total thickness deformation of cold rolling is greater than or equal to 60%, and no annealing is performed during the cold rolling process; the hot extrusion is: the extrusion temperature is 420°C, and the plate is extruded to the target thickness.
[0019] Preferably, in step (4), the solution treatment is a single-stage solution treatment or a double-stage solution treatment. The single-stage solution treatment is: heating at 450-550°C, keeping warm for 45-60 minutes, followed by rapid water quenching, and the transfer time is less than or equal to 15 seconds; the double-stage solution treatment is: keeping warm at 470°C for 30 minutes, then keeping warm at 505°C for 30 minutes, followed by rapid water quenching, and the transfer time is less than or equal to 15 seconds.
[0020] Preferably, the interval between the cold deformation treatment and the solution treatment in step (4) is less than or equal to 30 minutes.
[0021] Preferably, in step (4), the cold deformation treatment is rolling or stretching, and the deformation temperature range is -50°C to 50°C.
[0022] Preferably, in step (5), the aging treatment is single-stage aging or two-stage aging. The single-stage aging treatment is 80-120° C. for 48-720 h; the two-stage aging treatment is 120-195° C. for 10-30 minutes, and then 50-100° C. for 48-720 h.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention provides a method for preparing a high-strength and low fatigue crack growth rate aluminum alloy material. The process is simple and easy to operate. The powder making, hot isostatic pressing, plastic forming and heat treatment involved all meet industrial production conditions, and can realize the preparation and processing of high-strength and low fatigue crack growth rate aluminum alloy materials; through plastic processing and forming, the required materials such as plates can be formed.
[0025] The present invention provides a method for preparing a high-strength and low fatigue crack growth rate aluminum alloy material. Fine aluminum alloy powder can form a fine-grained structure with low dislocation density, and coarse powder can form a coarse-grained structure with high dislocation density, thereby realizing a heterogeneous grain microstructure design, wherein the fine-grained structure can improve the strength, and the coarse-grained structure can reduce the fatigue crack growth rate. The aging treatment process is combined to refine the precipitated phase and control the dislocation density, so that a strain gradient is formed near the interface of the coarse-fine grain region, and a heterogeneous strengthening effect can be induced, thereby ultimately improving the strength of the aluminum alloy material while making it have a lower fatigue crack growth rate. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0027] Example 1
[0028] (1) Pure Al was added to a crucible, and after melting at 780°C, Al-Cu, Al-Mn master alloy, and pure Mg ingot were added in sequence according to the alloy composition of Al-4.2Cu-1.8Mg-0.5Mn (mass fraction, %). After fully melting and stirring, the slag on the surface of the melt was removed. After standing and keeping warm for 15 minutes, the melt was flowed out through a ceramic guide tube and the gas atomization method (high pressure N2, pressure 10Mpa, flow rate 600m / s) was used to break the outflowing melt into droplets. Finally, the droplets solidified to form aluminum alloy spherical powder. Fine aluminum alloy powder and coarse aluminum alloy powder were screened out, wherein the average particle size of the fine aluminum alloy powder was 10 microns, and the average particle size of the coarse aluminum alloy powder was 50 microns. The average aspect ratio of the coarse and fine aluminum alloy powders was approximately 1, and the particle size distribution was approximately normal distribution.
[0029] (2) The fine aluminum alloy powder is 80% by mass and the coarse aluminum alloy powder is 20% by mass. The two alloy powders are fully mixed by mechanical mixing, and then a metal sheath is used. The heating temperature is 550°C and the vacuum degree inside the metal sheath is 0.1 Pa. Then, hot isostatic pressing is performed at a pressure of 100 MPa, a hot pressing temperature of 550°C, and a holding time of 8 hours. Then, the heat is continued for 12 hours without external pressure for homogenization treatment, and finally air cooling is performed. The density of the obtained aluminum alloy ingot is ~99.8%.
[0030] (3) Then the above aluminum alloy ingot is subjected to homogenization annealing treatment at a temperature of 500°C and a holding time of 6 hours, and then taken out and air-cooled. The aluminum alloy ingot after homogenization annealing is hot-rolled at a rolling start temperature of 420°C and rolled to a thickness of 6 mm, which is 2% of the thickness before hot rolling; then annealing treatment is performed at a temperature of 400°C and a holding time of 0.5 hours; after air cooling, cold rolling is performed, and after 15 passes of rolling, a 2 mm thick aluminum alloy sheet is obtained, and the cold rolling thickness deformation is 67%, and no annealing treatment is performed during the cold rolling process.
[0031] (4) The plate is then solution treated, and the solution treatment process is to keep it at 550℃ for 45min, followed by rapid water quenching, and the transfer time is less than 15s; after solution treatment, it is transferred to the rolling mill within 30min, cold rolled at -50℃, and the deformation is 3%.
[0032] (5) Finally, the plate is subjected to a single-stage aging treatment with the process parameters of 80°C for 720 hours.
[0033] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 460MPa, the tensile strength is 620MPa, the elongation is 18%; the stress intensity factor range ΔK is 20MPa.m 0.5 The fatigue crack growth rate is 4×10 -4 mm / cycle.
[0034] Example 2
[0035] The same points as Example 1 are not repeated here, except that the mass fraction of the fine aluminum alloy powder is 60%; the mass fraction of the coarse aluminum alloy powder is 40%.
[0036] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 445MPa, the tensile strength is 615MPa, the elongation is 20%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 3×10 -4mm / cycle.
[0037] Example 3
[0038] The similarities with Example 1 are not repeated here. The differences are as follows: adjusting the atomization process parameters (pressure 8 MPa, flow rate 300 m / s), and obtaining a fine alloy powder with an average particle size of 60 microns and a coarse aluminum alloy powder with an average particle size of 600 microns by screening; in step (4), the process for cold deformation of the plate is as follows: the deformation amount of cold rolling at 50°C is 30%; in step (5), the aging treatment is a two-stage aging treatment, and its process parameters are insulation at 195°C for 10 minutes and then insulation at 100°C for 48 hours.
[0039] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 440MPa, the tensile strength is 610MPa, and the elongation is 21%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 3.5×10 -4 mm / cycle.
[0040] Example 4
[0041] (1) Al-Zn-Mg-Cu alloy powder was used as raw material, and its specific alloy composition was Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr (mass fraction, %). The same method as in Example 1 was adopted, except that the atomization process parameters (pressure 9 MPa, flow rate 500 m / s) were adjusted, and fine aluminum alloy powder with an average particle size of 30 μm and coarse aluminum alloy powder with an average particle size of 200 μm were prepared by sieving. The average aspect ratio of the coarse and fine aluminum alloy powders was approximately 1, and the particle size distribution was approximately normal distribution.
[0042] (2) After the two alloy powders are fully mixed by mechanical mixing in a ratio of 60% by mass of fine aluminum alloy powder and 40% by mass of coarse aluminum alloy powder, a metal sheath is first used, the heating temperature is 450°C, and the vacuum degree inside the metal sheath is 0.1 Pa. Then, hot isostatic pressing is carried out at a pressure of 100 MPa, a hot pressing temperature of 450°C, and a holding time of 2 h. Then, the heat is continued for 24 h under no external pressure conditions for homogenization treatment, and finally air cooling is carried out. The density of the obtained aluminum alloy ingot is ~99.8%.
[0043] (3) The aluminum alloy ingot after hot isostatic pressing is then subjected to homogenization annealing at a temperature of 450°C for 12 hours, and then taken out for air cooling. The aluminum alloy ingot after homogenization annealing is hot extruded at an extrusion temperature of 420°C, and then extruded into a 5 mm thick plate.
[0044] (4) The plate is then solution treated at 450°C for 60 min, followed by rapid water quenching with a transfer time of less than 15 s; the plate is transferred to a stretching machine within 1 h and stretched at 25°C by 5%.
[0045] (5) Finally, the plate was subjected to a single-stage aging treatment with the process parameters of 120 °C for 48 h.
[0046] The room temperature mechanical properties test along the extrusion direction shows that the yield strength of Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr aluminum alloy sheet is 720MPa, the tensile strength is 760MPa, and the elongation is 12%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 8×10 -4 mm / cycle.
[0047] Example 5
[0048] The similarities with Example 4 are not repeated here. The differences are: adjusting the atomization process parameters (pressure 9 MPa, flow rate 500 m / s), and obtaining fine aluminum alloy powder with an average particle size of 30 microns and an average particle size of 200 microns by screening. The mass fraction of the fine aluminum alloy powder is 70%, and the mass fraction of the coarse aluminum alloy powder is 30%.
[0049] The room temperature mechanical properties test along the extrusion direction shows that the yield strength of Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr aluminum alloy sheet is 700MPa, the tensile strength is 740MPa, and the elongation is 13%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 7.5×10 -4 mm / cycle.
[0050] Example 6
[0051] The similarities with Example 4 are not repeated here. The differences are as follows: adjusting the atomization process parameters (pressure 9 MPa, flow rate 400 m / s), and obtaining fine aluminum alloy powder with an average particle size of 50 microns and coarse aluminum alloy powder with an average particle size of 300 microns by screening; the mass fraction of the fine aluminum alloy powder is 60%, and the mass fraction of the coarse aluminum alloy powder is 40%; the aging process is a two-stage aging treatment, and the process parameters are 120°C insulation for 30 min, and then 50°C insulation for 720 h.
[0052] The room temperature mechanical properties test along the extrusion direction shows that the yield strength of Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr aluminum alloy sheet is 710MPa, the tensile strength is 750MPa, and the elongation is 12%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 8.5×10 -4 mm / cycle.
[0053] Example 7
[0054] The same as Example 6 is not repeated here, except that: the aluminum alloy powder used is Al-4.2Cu-1.8Mg-0.5Mn (mass fraction, %) and Al-6.2Zn-2.3Mg-2.3Cu-0.2Zr-0.1Sc. The fine aluminum alloy powder with an average particle size of 50 microns is composed of Al-4.2Cu-1.8Mg-0.5Mn and the coarse aluminum alloy powder with an average particle size of 200 microns is composed of Al-6.2Zn-2.3Mg-2.3Cu-0.2Zr-0.1Sc, the mass fraction of the fine aluminum alloy powder is 60%, and the mass fraction of the coarse aluminum alloy powder is 40%. The solid solution treatment adopts a two-stage solid solution treatment, the temperature is 470℃ for 30min, and then 505℃ for 30min, followed by rapid water quenching, and the transfer time is less than or equal to 15s; cold deformation treatment is immediately carried out after water quenching, and the thickness deformation of room temperature rolling is 5%. Finally, a two-stage aging treatment was carried out, with a temperature of 180°C for 10 min and then a temperature of 80°C for 720 h.
[0055] The room temperature mechanical property test along the extrusion direction shows that the yield strength of the aluminum alloy sheet is 560MPa, the tensile strength is 690MPa, the elongation is 14%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 7×10 -4 mm / cycle.
[0056] Comparative Example 1
[0057] The implementation steps of this comparative example are basically the same as those of Example 1, except that:
[0058] The Al-Cu-Mg plate is prepared by alloy powder with a single particle size distribution, and the average particle size of the alloy powder is 10 microns; the aging process adopts a conventional aging treatment process, and the process parameters are 180°C insulation for 20 hours, and there is no cold deformation treatment before aging.
[0059] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 320MPa, the tensile strength is 490MPa, the elongation is 16%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 6.5×10 -4 In comparison, the yield strength, tensile strength and elongation of the material in Example 1 of the present invention are all improved, while the fatigue crack growth rate is significantly reduced.
[0060] Comparative Example 2
[0061] The implementation steps of this comparative example are basically the same as those of Example 1, except that the Al-Cu-Mg plate is prepared by using alloy powder with a single particle size distribution, and the average particle size of the alloy powder is 10 microns.
[0062] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 460MPa, the tensile strength is 580MPa, the elongation is 12%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 7.5×10 -4 In comparison, the tensile strength and elongation of the material in Example 1 of the present invention are both improved, while the fatigue crack growth rate is reduced by nearly two times.
[0063] Comparative Example 3
[0064] The specific steps of this comparative example are basically the same as those of Example 1, except that: the aging treatment adopts conventional aging treatment, the specific aging process parameters are 180° C. insulation for 20 hours, and there is no cold deformation treatment before aging.
[0065] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 300MPa, the tensile strength is 485MPa, the elongation is 17%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 6×10 -4 Compared with this, the strength and elongation of Example 1 of the present invention are improved simultaneously, while the fatigue crack growth rate is reduced.
[0066] Comparative Example 4
[0067] The specific steps of this comparative example are basically the same as those of Example 1, except that the aging treatment adopts conventional aging treatment, and the specific aging process parameters are 180° C. insulation for 20 hours.
[0068] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 450MPa, the tensile strength is 575MPa, the elongation is 11%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 7.5×10 -4 In comparison, the strength and elongation of the material in Example 1 of the present invention are both improved while the fatigue crack growth rate is reduced by nearly two times.
[0069] Comparative Example 5
[0070] The implementation steps of this comparative example are basically the same as those of Example 2, except that the Al-Cu-Mg plate is prepared by alloy powder with a single particle size distribution and a conventional aging treatment process, the average particle size of the alloy powder is 200 μm, the aging process parameters are 180° C. insulation for 20 h, and no cold deformation treatment is performed before aging.
[0071] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 280MPa, the tensile strength is 470MPa, the elongation is 18%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 5.5×10 -4 In comparison, the strength and elongation of the material in Example 2 of the present invention are both improved while the fatigue crack growth rate is reduced by nearly two times.
[0072] Comparative Example 6
[0073] The specific steps of this comparative example are basically the same as those of Example 2, except that the Al-Cu-Mg plate is prepared by using alloy powder with a single particle size distribution, and the average diameter of the powder is 10 microns.
[0074] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 380MPa, the tensile strength is 510MPa, the elongation is 16%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 7×10 -4 In comparison, the strength and elongation of the material in Example 2 of the present invention are both improved while the fatigue crack growth rate is reduced by more than 2 times.
[0075] Comparative Example 7
[0076] The specific steps of this comparative example are basically the same as those of Example 3, except that the Al-Cu-Mg plate is prepared by using alloy powder with a single particle size distribution, and the average diameter of the powder is 600 microns.
[0077] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 220MPa, the tensile strength is 450MPa, the elongation is 18%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 5×10 -4 In comparison, the strength and elongation of the material in Example 3 of the present invention are both improved, while the fatigue crack growth rate is significantly reduced.
[0078] Comparative Example 8
[0079] The specific steps of this comparative example are basically the same as those of Example 3, except that the Al-Cu-Mg plate adopts a conventional aging process, and the specific process parameters are 180° C. insulation for 20 hours.
[0080] The room temperature mechanical properties test along the rolling direction shows that the yield strength of Al-4.2Cu-1.8Mg-0.5Mn aluminum alloy sheet is 270MPa, the tensile strength is 475MPa, the elongation is 18%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 5.5×10 -4 In comparison, the strength and elongation of the material in Example 3 of the present invention are both improved, while the fatigue crack growth rate is significantly reduced.
[0081] Comparative Example 9
[0082] This comparative example is basically the same as Example 4, except that alloy powder with a single particle size distribution is used, and its average particle size is 200 microns.
[0083] The room temperature mechanical properties test along the extrusion direction shows that the yield strength of Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr aluminum alloy sheet is 660MPa, the tensile strength is 690MPa, and the elongation is 8%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 1.0×10 -3 In comparison, the strength and elongation of the material in Example 4 of the present invention are both improved while the fatigue crack growth rate is significantly reduced.
[0084] Comparative Example 10
[0085] This comparative example is basically the same as Example 4, except that: alloy powder with a single particle size distribution and a conventional aging treatment process are used, the average particle size is 30 microns, the aging treatment process parameters are 120° C. insulation for 20 hours, and no cold deformation treatment is performed before aging.
[0086] The room temperature mechanical properties test along the extrusion direction shows that the yield strength of Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr aluminum alloy sheet is 675MPa, the tensile strength is 700MPa, and the elongation is 7%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 1.5×10 -3 In comparison, the strength and elongation of the material in Example 4 of the present invention are both improved while the fatigue crack growth rate is significantly reduced.
[0087] Comparative Example 11
[0088] This comparative example is basically the same as Example 6, except that: alloy powder with a single particle size distribution and a conventional aging process are used, the average particle size is 50 microns, the aging process parameters are 120° C. insulation for 20 hours, and no cold deformation treatment is performed before aging.
[0089] The room temperature mechanical properties test along the extrusion direction shows that the yield strength of Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr aluminum alloy sheet is 680MPa, the tensile strength is 710MPa, the elongation is 10%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 1×10 -3 In comparison, the strength and elongation of the material in Example 6 of the present invention are both improved while the fatigue crack growth rate is significantly reduced.
[0090] Comparative Example 12
[0091] This comparative example is basically the same as Example 6, except that conventional aging treatment is adopted, the process parameters of which are 120°C insulation for 20 hours, and no cold deformation treatment is performed before aging.
[0092] The room temperature mechanical properties test along the extrusion direction shows that the yield strength of Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr aluminum alloy sheet is 620MPa, the tensile strength is 670MPa, and the elongation is 11%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 9.3×10 -4 In comparison, the strength and elongation of the material in Example 6 of the present invention are both improved while the fatigue crack growth rate is significantly reduced.
[0093] Comparative Example 13
[0094] This comparative example is basically the same as Example 7, except that conventional aging treatment is adopted, the process parameters of which are 180°C insulation for 20 hours, and no cold deformation treatment is performed before aging.
[0095] The room temperature mechanical property test along the extrusion direction shows that the yield strength of the aluminum alloy sheet is 450MPa, the tensile strength is 570MPa, the elongation is 12%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 8.0×10 -4 In comparison, the strength and elongation of the material in Example 7 of the present invention are both improved while the fatigue crack growth rate is significantly reduced.
[0096] The specific embodiments of the present invention are described above. It can be seen from Examples 1-7 that the method provided by the present invention can be applied to different alloy materials, and can improve the strength, elongation and fatigue crack propagation resistance of different alloy materials. By comparing Examples 1-3 with Comparative Examples 1-8, Examples 4-6 with Comparative Examples 9-12, and Example 7 with Comparative Example 13, the method of the present invention provides a method for preparing a high-strength and low fatigue crack propagation rate aluminum alloy material. Due to the use of coarse and fine powders of specific particle sizes for proportioning, the material is treated under aging treatment conditions different from conventional aging treatment processes, and combined with processes such as cold deformation treatment, the strength, elongation and fatigue crack propagation resistance of the aluminum alloy can be improved at the same time.
[0097] It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments may be combined with each other at will.
Claims
1. A method for preparing a high-strength and low fatigue crack growth rate aluminum alloy material, characterized in that: The steps include: (1) screening two types of aluminum alloy powders with different particle size distributions, the first type being fine aluminum alloy powder with an average particle size of 10-60 μm, wherein the weight of the fine aluminum alloy powder accounts for 60%-80%; the second type being coarse aluminum alloy powder with an average particle size of 50-600 μm; (2) After the fine aluminum alloy powder and the coarse aluminum alloy powder are fully mixed, vacuum degassing and hot isostatic pressing are performed to obtain an aluminum alloy ingot with a density of ≥99.5%; (3) subjecting the aluminum alloy ingot to homogenization annealing treatment, air cooling, and then plastic forming to obtain a heterogeneous aluminum alloy material having a coarse-fine grain distribution; (4) subjecting the above-mentioned heterogeneous structure aluminum alloy material containing a coarse-fine grain distribution to a solution treatment, wherein the solution treatment comprises heating, heat preservation and water quenching steps; after the solution treatment, a cold deformation treatment is performed, wherein the deformation amount is 3%-30%, and the interval time with the end of the solution treatment is less than or equal to 1 hour; and the deformed heterogeneous structure aluminum alloy material is obtained; (5) The deformed heterogeneous aluminum alloy material is subjected to single-stage aging or two-stage aging treatment.
2. The method for preparing a high-strength and low-fatigue crack growth rate aluminum alloy material according to claim 1, characterized in that: The coarse aluminum alloy powder and the fine aluminum alloy powder are approximately spherical.
3. The method for preparing a high-strength and low-fatigue crack growth rate aluminum alloy material according to claim 1, characterized in that: The ratio of the average particle size of the coarse aluminum alloy powder to the average particle size of the fine aluminum alloy powder is 5-10.
4. The method for preparing a high-strength and low-fatigue crack growth rate aluminum alloy material according to claim 1, characterized in that: In the step (2), the vacuum degassing and hot isostatic pressing treatment is as follows: first, a metal sheath is used, the heating temperature is 450-550°C, the vacuum degree inside the metal sheath is greater than or equal to 0.1Pa, and then hot isostatic pressing is performed, the pressure is greater than or equal to 100MPa, the hot pressing temperature is 450-550°C, the holding time is 2-8h, and then the heat preservation is continued for 12-24h without external pressure for homogenization treatment, and finally air cooling is performed, and the density of the obtained aluminum alloy ingot is ≥99.5%.
5. The method for preparing a high-strength and low fatigue crack growth rate aluminum alloy material according to claim 1, characterized in that: The homogenization annealing treatment in step (3) is performed at 450-500° C. and the holding time is 6-12 hours; the plastic processing forming method in step (3) is hot rolling or hot extrusion.
6. The method for preparing a high-strength and low-fatigue crack growth rate aluminum alloy material according to claim 5, characterized in that: The hot rolling process includes: the rolling start temperature is 420°C, the hot rolling is terminated when the total thickness deformation is greater than or equal to 98%, and annealing is performed, the annealing temperature is 400°C, the temperature is kept for 0.5h, cold rolling is performed after air cooling, and aluminum alloy thin plates are formed through multiple rolling passes, the total thickness deformation of cold rolling is greater than or equal to 60%, and no annealing is performed during the cold rolling process; the hot extrusion process includes: the extrusion temperature is 420°C, and the plates are extruded to the target thickness.
7. The method for preparing a high-strength and low-fatigue crack growth rate aluminum alloy material according to claim 1, characterized in that: In the step (4), the solution treatment is a single-stage solution treatment or a double-stage solution treatment. The single-stage solution treatment is as follows: heating at a temperature of 450-550°C, keeping warm for 45-60 minutes, followed by rapid water quenching, and the transfer time is less than or equal to 15 seconds; the double-stage solution treatment is as follows: keeping warm at a temperature of 470°C for 30 minutes, then keeping warm at 505°C for 30 minutes, followed by rapid water quenching, and the transfer time is less than or equal to 15 seconds.
8. The method for preparing a high-strength and low fatigue crack growth rate aluminum alloy material according to claim 1, characterized in that: In the step (4), the cold deformation treatment is rolling or stretching, and the deformation temperature ranges from -50°C to 50°C.
9. The method for preparing a high-strength and low-fatigue crack growth rate aluminum alloy material according to claim 1, characterized in that: In the step (5), the single-stage aging treatment is 80-120°C, and the temperature is kept for 48h-720h; the two-stage aging treatment is: 120°C-195°C, and the temperature is kept for 10-30min, and then 50-100°C, and the temperature is kept for 48h-720h.
Citation Information
Patent Citations
Processing technique for improving fatigue damage resistance of 2XXX series aluminum alloy plate
CN105603340A
Preparation method of multi-grain-scale reinforced aluminum alloy material
CN110343886A
Powder metallurgy high-strength high-conductivity heat-resistant aluminum conductor and preparation method thereof
CN114999709A
Micro-nano synergistically reinforced heterogeneous metal matrix composite material and graded assembly preparation
CN116103530A
High-toughness complex cupronickel alloy material and preparation method thereof
CN116891962A